A Sociological Analysis of the Space of Popular Music Production in Iran - Samim, Reza; Ghasemi, Vahid; Fatemi, Sasan (Mediterranean Journal of Social Sciences, 2012)
Different research and theoretical approaches have been adopted in the study of the space of music production. In thepresent study, which relies on the ethnographic/sociological research approach in the study of cultural producers, because of theimpossibility of conducting a structural research on the space of popular music production in Iran due to lack of reliable statistics on thespace of production, We have tried to analyze this space with the aid of a sociological conceptualization at a micro level, using the datacollected from two interviews with the official and unofficial producers of popular music in Tehran. In order to collect qualitative data toanswer the question as to whether the action among the producers of popular music in Iran, as the main constructors of the space ofmusic production, is an ideological action, the focus group technique has been used. The data was collected through five sessions ofdiscussion with two eight-member groups, and was analyzed using the reflective analysis method. The data analysis shows that sincethe producers of the discussed genres, as the actors of this space, are ideological, the space of production of popular music in Iran is acontroversial space where no hybrid of cognitive music is possible. From the viewpoint of the authors of the present article the hybrid ofcognitive music seems to be the only way to overcome the cultural dismorphy existing in the space of music production in Iran.